Antihyperglycemic Karamunting Leaf Extract (Rhodomyrtus tomentosa (Aiton) Hassk) in Alloxan Induced Wistar Strain Male Rats - Sternatami Liberitera; Indah Solihah; Yuni Eka Sari (Jurnal Penelitian Sains, 2023)
Diabetes Mellitus (DM) is an endocrine disease characterized by an abnormal increase in blood glucose levels. Prevention of DM complications could be avoided by using antihyperglycemic therapy. Thus, may increase the risk of adverse effects. The discovery of antihyperglycemic compounds from medicinal plants was carried out to avoid adverse effects. One of the medicinal plants that has antihyperglycemic potential is karamunting (Rhodomyrtus tomentosa (Aiton) Hassk). This study was aimed to examine the antihyperglycemic activity of karamunting leaf extract and the compounds present in the extract with the highest activity. Activity test was carried out in vivo using Wistar strain male white rats. Extraction was carried out by multilevel maceration using n-hexane, ethyl acetate, and 96% ethanol as solvents. There were 6 treatment groups, namely the normal group, positive control, negative control, n-hexane extract, ethyl acetate extract, and 96% ethanol extract. The positive control was glibenclamide and the negative control was 0.5% Na CMC. Identification of the compounds contained in the extract was carried out by phytochemical screening. Statistical data analysis using one way ANOVA. The results showed that 96% ethanol extract of karamunting leaves had the best activity in reducing blood glucose levels with a decrease of 40%. The statistical test results showed a significant difference between each treatment group (p<0.05). In 96% ethanol extract of karamunting leaves, flavonoids, phenols, tannins and saponins were identified.Â Keywords: Extract, Hypoglicemia, KaramuntingÂ